Stunting Reduction through Healthy Baby Education in Wironanggan Village, Sukoharjo - Samiyem, Samiyem; Muhammad Raihan Ishad; Arif Pristianto; Farid Rahman; Taufik Eko Susilo; Adnan Faris Naufal; Tiara Fatmarizka (Universitas Muhammadiyah Surakarta, 2025)
Stunting is a serious issue affecting children's growth and development, caused by various factors such as chronic malnutrition, infection, and lack of parental knowledge. Based on field observation in Wironanggan Village, Sukoharjo, it was found that 15 children were experiencing stunting in 2024. This community service program aimed to increase parental awareness and knowledge about stunting through a healthy baby competition method combined with nutritional education. The implementation method included observation, preparation, execution, and evaluation stages. The event was held at Anggrek Posyandu, involving 30 children aged 1–3 years and their parents. Nutritional status was assessed through body weight, height, mid-upper arm circumference, and head circumference measurements, followed by educational sessions using leaflets and an interactive lecture method. Results showed an increase in parental enthusiasm and knowledge after the activity. Moreover, the healthy baby competition successfully motivated parents to strive for better child development outcomes. The program concluded with the distribution of supplementary foods (PMT), such as fruits and milk, supporting daily nutritional needs. This activity proved the effectiveness of an educational and participatory approach in tackling stunting at the village level.